Endangered Hayu Culture in Nepal; Historical Legacy of Marginalization - Hayu , Talak Bahadur (HISAN: Journal of History Association of Nepal, 2024)
This paper explores the rich cultural history of the Hayu people of Nepal, emphasizing the significant impact of their ongoing marginalization. Officially recognized by the Nepalese government as one of the most vulnerable ethnic groups, the Hayu face numerous social, economic, and political challenges. These issues are deeply rooted in systemic discrimination, notably the caste hierarchy formalized by the 1854 AD Civil Code, which labelled the Hayu as "Masinya Matawali" or enslaveable alcohol drinkers. This historical marginalization has contributed to restricted access to education, employment, and essential services for the Hayu community. Drawing from both historical and contemporary data, this paper examines the intersection of Hayu cultural identity, marginalization, and survival. It highlights briefly their unique language, traditions, and clan systems while stressing the urgent need for reforms to protect their cultural heritage and improve their living conditions. The study aims to provide a deeper understanding of ethnic marginalization in Nepal and advocate for inclusive policies for all indigenous minorities and endangered.